Performance of the Electro-Fenton Process in Reducing COD and TSS in Cigarette Industry Wastewater - Izzuddin Ahmad Faza; Restu Hikmah Ayu Murti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Cigarette industry wastewater contains organic compounds and suspended solids that may adversely affect receiving water bodies when discharged without adequate treatment. This study evaluated the effects of aeration time, electric current, and contact time on dissolved oxygen (DO), chemical oxygen demand (COD), and total suspended solids (TSS) concentrations during Electro-Fenton treatment. The experiment was conducted in batch mode using a 3 L reactor, with aeration times of 0, 5, and 10 minutes, electric currents of 3, 4, and 5 A, and contact times of 10, 15, 20, 25, and 30 minutes. The initial wastewater characteristics were pH 4.8, DO 0 mg/L, COD 1,017 mg/L, and TSS 56 mg/L. Aeration increased the initial DO concentration to approximately 5.3 mg/L after 5 minutes and 6.9–7.1 mg/L after 10 minutes. The lowest final COD concentration, approximately 150 mg/L, was obtained at an electric current of 5 A, an aeration time of 10 minutes, and a contact time of 30 minutes. The lowest TSS concentration, approximately 10 mg/L, was observed at a contact time of 10 minutes under several treatment conditions. Longer contact times generally increased the TSS concentration, which was associated with the continued formation of iron-containing solids and flocs. These findings demonstrate that aeration time, electric current, and contact time influence COD and TSS concentrations during Electro-Fenton treatment of cigarette industry wastewater. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production